Answers

2015-10-02T13:04:46+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
To multiply a binomial by another binomial, you should multiply the two terms of the first binomial by the two terms of the second binomial using a method called foil, and then combine like terms to simplify.
Or simply use distributive property to solve it, just like on whole numbers:
(4 + 3) (3 - 4)
4 x 3 = 12
4 x -4 = -16
3 x 3 = 9
3 x -4 = -12
12 -16 +9 -12
-7
Ex.
Solve:
(4x + y)(7x - y)
+4x · +7x = 
+4x · -1y =
+1y · +7x = 
+1y · -1y =

(Find if the product is going to be + or -)

+4x · +7x = +
+4x · -1y = -
+1y · +7x = +
+1y · -1y = -

(Multiply the numerical coefficients by the other)

+4x · +7x = +28
+4x · -1y = -4
+1y · +7x = +7
+1y · -1y = -1

(Add the literal coefficients by the other)

+4x · +7x = +28x²
+4x · -1y = -4xy
+1y · +7x = +7xy
+1y · -1y = -1y²

(Write the equation ----------- form)

28x² - 4xy + 7xy - 1y²

(Simplify by combining like terms)

28x² + 3xy - y² 
is the answer.

Same method is applied on trinomials, and multinomials. 









0